Conclusions: patterns of Europeanization and policy change in the renewable energy policy domain - Jörgens, H.; Öller, E.; Solorio, I. (A guide to EU renewable energy policy: comparing europeanization and domestic policy change in EU member states, 2017)
In the second half of the 2010s, the transformation of the energy systems of the European Union (EU) and its member states towards a greater incorporation of renewable energy sources (RES) has come to a crossroads. While the 1990s and most of the 2000s witnessed a rapid increase in policies and programmes aimed to promote the production and consumption of energy from RES, and an equally rapid growth of the share of RES in national and European energy mixes, since the late 2000s the speed of transformation has slowed down considerably and instances of policy dismantling are becoming more frequent. Drawing on the rich empirical and analytical background of the book’s country studies, this concluding chapter adopts a comparative perspective in order to identify more general patterns of Europeanization and policy change in the renewable energy policy domain over the past decades. Focusing on the development and implementation of major renewable energy directives in the electricity and biofuels domains, the chapter sheds light on the complex patterns of renewable energy governance in the European Union, paying particular attention to the processes of bottom-up, top-down and horizontal Europeanization, as well the domestic drivers of (and obstacles to) transformative policy change. The empirically rich comparative analysis furthers our understanding of the structural and practical barriers that a RES-based energy transition in Europe and abroad is currently facing and sheds light on strategies and best practices for future renewable energy policy in the European multilevel polity. Keywords: biofuels policy, bottom-up Europeanization, horizontal Europeanization, renewable electricity policy, renewable energy policy, top-down Europeanization